Assessment and Optimization of the Insecticidal Properties of γ-Al2O3 Nanoparticles Derived from Mentha pulegium By-Products to Xylosandrus crassiusculus (Carob Beetle) - Abdoul-Latif, Fatouma Mohamed; Ainane, Ayoub; Eddabbeh, Fatima-Ezzahra; Oumaskour, Khadija; Mohamed, Jalludin; Abu Arra, Ahmad; Ainane, Tarik (MDPI, 2024)
This study concentrates on assessing the insecticidal attributes of the gamma-Al2O3 nanoparticles derived from the remnants of Mentha pulegium, which include essential oil, ethanolic extract, and plant waste. The synthesis of the gamma-Al2O3 nanoparticles was executed using a direct sol-gel procedure, affirming the crystal structure according to extensive physicochemical analyses such as UV-Vis, XRD, FTIR, and SEM. Evaluation of the insecticidal activity in vitro was conducted against Xylosandrus crassiusculus, a pest that infests carob wood, utilizing strains from diverse forests in the Khenifra region, situated in the Moroccan Middle Atlas. The lethal doses 50 ranged from 40 mg/g to 68 mg/g, indicating moderate effectiveness compared to the commercial insecticide Permethrin. Optimization of the conditions for the efficiency of the gamma-Al2O3 nanoparticles was determined using experimental plans, revealing that time, humidity, and temperature were influential factors in the lethal dose 50 of these nanomaterials. Moreover, this study encompasses the establishment of correlations using Principal Component Analysis (PCA) and Ascending Hierarchical Classification (AHC) among various geographic, biological, and physical data, amalgamating geographic altitude and gamma-Al2O3 nanoparticle insecticide parameters, as well as the attributes of the mechanical tests conducted on the carob wood affected by insects. The correlations highlight the close connections between the effectiveness of the insecticide, mountain altitude, and the mechanical parameters that were examined. Ultimately, these nanoparticles demonstrate promising potential as alternative insecticides, thus opening up encouraging prospects for safeguarding against carob wood pests.
Keywords: gamma-Al2O3 nanoparticles; insecticidal properties; mechanical tests; carob; wood beetle; optimization; TITANIUM-DIOXIDE; ALUMINUM-OXIDE; ZINC-OXIDE; ALPHA-AL2O3; Biochemistry & Molecular Biology; Chemistry